Menyoal Metode Perkuliahan Daring, Transfer Nilai Pendidikan atau Presensi Kehadiran Belaka? - Ahmad Riyadh Maulidi; Surawardi Surawardi (PAKAR Pendidikan, 2020)
Lecture is one form of the education process. The most important thing in an education is the change in behavior gained from the transfer of values ​​or morals. The Covid-19 pandemic which had already spread to Indonesia made the lecture system, which was initially conducted face-to-face, be changed to an online system. When this system was implemented it turned out that the essence of education began to be set aside. Lectures are only seen as a formality. In fact, someone can already be considered learning if he has filled in the presence in the online lecture application comment column. It is interesting for researchers to discuss the phenomenon as an effect caused during a pandemic. The method used is the method of observation and the method of literature by finding sources of reference related to educational theories. The results of this study indicate that the online lecture method already shows symptoms of ignoring transfer of values ​​or morals. So cooperation is needed from various parties so that the meaning of learning with this online system remains conveyed.